Welfare experiences of Portuguese Angolan miners: A longitudinal comparative study, 1918-1974 - Leo Dolan (African Economic History Network (AEHN), 2023)
This paper provides the first quantitative assessment of living standards in Angola during the colonial period, with a specific focus on the Companhia de Diamantes de Angola (Diamang), the largest and most profitable company in Portuguese colonial history. Employing the "barebones subsistence basket" deflation method to measure welfare ratios, the paper examines the progression of living standards from 1918 to 1974. The research findings illustrate a significant shift from below-subsistence wages to an unprecedented rise in welfare ratios after 1960, signifying a remarkable deviation from the welfare trajectory observed in other colonial empires. By presenting the first comprehensive and high-quality dataset covering an extensive time frame, exclusively dedicated to examining worker living standards in colonial Portuguese Africa, this study challenges conventional perspectives on the outcomes of extractive labour regimes. Furthermore, it establishes a precedent for the importance of further exploration into other neglected colonial contexts. Consequently, this research not only contributes to the discourse on economic history but also enhances our understanding of Africa's distinctive colonial experiences.
Keywords: F54; I3; J3; J47; N57; 330; Angola; Coercive Labor; Colonialism; Diamond Mining; wages